2007
DOI: 10.1074/jbc.m512337200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Region of Troponin I Important in Signaling Cross-bridge-dependent Activation of Cardiac Myofilaments

Abstract: Force generating strong cross-bridges are required to fully activate cardiac thin filaments, but the molecular signaling mechanism remains unclear. Evidence demonstrating differential extents of cross-bridge-dependent activation of force, especially at acidic pH, in myofilaments in which slow skeletal troponin I (ssTnI) replaced cardiac TnI (cTnI) indicates the significance of a His in ssTnI that is an homologous Ala in cTnI. We compared cross-bridge-dependent activation in myofilaments regulated by cTnI, ssTn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…30 Furthermore, we have reported that the cTnI N-terminal region surrounding Ala66, a region that strongly interacts with the cTnC C-lobe, is a significant locus of signaling in the activation of the thin filament by strongly bound cross-bridges. 31 Together with these previous findings, our current results provide further evidence indicating a unique role for the cTnC C-lobe interaction with the cTnI N terminus in myofilament contractile regulation.…”
Section: Discussionsupporting
confidence: 72%
“…30 Furthermore, we have reported that the cTnI N-terminal region surrounding Ala66, a region that strongly interacts with the cTnC C-lobe, is a significant locus of signaling in the activation of the thin filament by strongly bound cross-bridges. 31 Together with these previous findings, our current results provide further evidence indicating a unique role for the cTnC C-lobe interaction with the cTnI N terminus in myofilament contractile regulation.…”
Section: Discussionsupporting
confidence: 72%
“…However, the relative orientation of the ITarm to actin filament axis is more sensitive to strong cross-bridge attachment than to Ca 2+ -binding to the regulatory sites [41]. Moreover, recent data indicate that the IT-arm region is involved in the cross-bridge dependent activation of myofilaments [21]. These studies demonstrated that a region of cTnI in the near N-terminal region (surrounding Ala-65), which interacts with C-terminal regions of cTnC and cTnT, is of particular significance in transducing signaling of thin filament activation by strong cross-bridges.…”
Section: Molecular Mechanisms Of Ctni Function In Ca2+ and Crossbridgmentioning
confidence: 99%
“…Apart from their significant effects on cardiac dynamics, cTnI phosphorylation at the PKA sites affects length dependence of activation (LDA) [20]. Cooperative mechanisms involving feedback effects of strongly bound cross-bridges are important for LDA and are also sensitive to isoform specific structure in cardiac TnI [21].…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%
“…At low [Ca 2ϩ ], the Ca 2ϩ -regulated on rate of cTn becomes negligible, and the overall dynamics of the thin filament (k on ϩ k off ) among off and on states become slowest, i.e., just determined by k off (7). Troponin containing ssTnI has been shown to have a three times slower rate of Ca 2ϩ dissociation from TnC (k off ) compared with troponin containing cTnI (8). This is in agreement with the enhanced Ca 2ϩ sensitivity of myofibrils containing ssTnI, compared to myofibrils containing cTnI found by de Tombe et al (6).…”
mentioning
confidence: 99%